Orientalism updated: aesthetics of Orientalism after 9/11 and the war on Iraq between truth and fiction - Maasarani, Mohammad Noah (2018)
World perception is governed by an us-versus-them binary mode of thought, which has been tackled as “Orientalism” in Edward Said’s book of the same title, in which he shows the discursive nature of this pattern and shows its dissemination across scholarly work, fictional novels, travel literature, paintings and other works. However, to talk about Orientalism now is to talk about a stagnant academic debate over what counts as orientalist and what does not, and to discuss whether the word “Orientalist” is in any way derogatory. This debate and the notion of Orientalism as racism come from the association of Orientalist representations with an idea of a “truth” behind them. Fictional works fluctuate between a notion of representation, and an artistic license to produce whatever sells to the majority of the public. Orientalism only exists through the passive acceptance of such divisions. Edward Said began his project at this point of general passivity, but the weight of a categorical system of knowledge division weighed down on him, protecting the pure notion of “truth” and the way it reproduces its own “passivity” that is constituent of Orientalism and of representation by and large. While the textual academic debate on Orientalism remains stuck in a deadlock of mutual accusations of deliberate distortion, Orientalism itself continues in the melange of truth and fiction, across the images that dominate and shape our world, strategically making use of the blur of categories to defend itself against such criticism. Seeing Orientalism as a representational system, where the category and a mode of suitability is what determines whether something is in or out, sheds a new light on the power of this reproductive social system of expectations. By drawing upon the aesthetics of Orientalism, building upon theorists of the image, like Jacques Rancière, W.J.T. Mitchell, and Jean Baudrillard, this thesis aims to update Said’s theory by returning Orientalism to its image-based nature, and by looking at the ways in which an image has the capacity to structure a history of divisions, and to highlight the ways in which this continuity is achieved and how it is maintained in the new world of moving images, to affect the same binarism that constructs its own passive subjectivity.